Implementation Of Ctl To Strengthen Sq And Character Education In Islamic Religious Education Learning At SMPN 32 Bandung - Suryati, Yuli; Sukandar, Ahmad (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
This study aims to evaluate the effectiveness of implementing Contextual Teaching and Learning (CTL) in strengthening Spiritual Quotient (SQ) and character education within Islamic Religious Education (PAI) instruction at SMPN 32 Bandung. The research employed a quasi-experimental pre-test/post-test control group design involving two groups of students—one receiving CTL-based instruction and the other conventional teaching methods. A total of 60 students participated over an eight-week intervention period. Data were analyzed using ANCOVA to control for baseline differences, along with tests for normality and variance homogeneity. The findings revealed a significant improvement in the experimental group’s scores for SQ (Δ = +22.6; p < 0.001), moral virtue (Δ = +17.8; p < 0.005), and civic responsibility (Δ = +24.5; p < 0.001), with large effect sizes (η² ≥0.25). Qualitative data from teacher and student interviews also indicated positive perceptions regarding student motivation and the contextual relevance of learning. In conclusion, CTL-based PAI instruction was more effective than conventional methods in enhancing SQ and character dimensions, while also aligning with the core principles of the Kurikulum Merdeka. It is recommended that schools adopt CTL-integrated modules supported by authentic assessment and stakeholder collaboration. Future studies may explore long-term retention and mediating variables such as student motivation and social support